2018
DOI: 10.1177/0886260518780778
|View full text |Cite
|
Sign up to set email alerts
|

“A Lightbulb Moment”: Using the Theory of Planned Behavior to Explore the Challenges and Opportunities for Early Engagement of Australian Men Who Use Violence in Their Relationships

Abstract: Intimate partner violence (IPV) is a common complex social and public health problem. Interventions for IPV male perpetrators are an essential component of an early and effective response. Yet little is known about how to engage men in interventions for help-seeking. Using the theory of planned behavior (TPB), we explored men's perceptions of seeking help for an unhealthy relationship and how they could be supported to recognize their behavior and undertake change at an early stage. We recruited 23 men who wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…There is a paucity of literature on the individual characteristics of perpetrators of IPSV, although some research has examined traits associated with perpetration of sexual assault (Loh, Gidycz, Lobo, & Luthra, 2005;Tharp et al, 2013) and IPV (Love, Spencer, May, Mendez, & Stith, 2018) more broadly (World Health Organization, 2010). In the IPV context, the role of "hegemonic masculinity" (Connell, 1987) (often referred to as "support for traditional gender roles" or "hyper masculinity") has been acknowledged as being central (Forsdike, Tarzia, Flood, Vlais, & Hegarty, 2018;Peralta & Tuttle, 2013), both as a force that shapes violence-supportive attitudes, and as a trigger for violent acts when it is threatened (Anderson & Umberson, 2001;Gallagher & Parrott, 2011). Peralta and Tuttle (Peralta & Tuttle, 2013), for instance, have highlighted the relationship between IPV perpetration and threats to masculinity in the context of financial insecurity.…”
Section: Discussionmentioning
confidence: 99%
“…There is a paucity of literature on the individual characteristics of perpetrators of IPSV, although some research has examined traits associated with perpetration of sexual assault (Loh, Gidycz, Lobo, & Luthra, 2005;Tharp et al, 2013) and IPV (Love, Spencer, May, Mendez, & Stith, 2018) more broadly (World Health Organization, 2010). In the IPV context, the role of "hegemonic masculinity" (Connell, 1987) (often referred to as "support for traditional gender roles" or "hyper masculinity") has been acknowledged as being central (Forsdike, Tarzia, Flood, Vlais, & Hegarty, 2018;Peralta & Tuttle, 2013), both as a force that shapes violence-supportive attitudes, and as a trigger for violent acts when it is threatened (Anderson & Umberson, 2001;Gallagher & Parrott, 2011). Peralta and Tuttle (Peralta & Tuttle, 2013), for instance, have highlighted the relationship between IPV perpetration and threats to masculinity in the context of financial insecurity.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent Australian study, male perpetrators from a men's behaviour change program called for the 'right person' to be asking the 'right questions' to enable self-awareness of behaviour and enact change. 23 GPs could potentially fulfil this role, and are therefore encouraged to move away from the image of a male patient disclosing, 'I'm bashing my wife', and to instead use appropriate language to promote an opportunity for discussion to occur. 16 Engaging perpetrators and getting them to recognise and discuss their use of violence was a particular concern of the participants.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding IPA, we focus on research with male perpetrators and female victims, and where male samples are diverse, for example, in terms of ethnicity (e.g., Holtrop et al, 2017) Qualitative Research on IPA/Substance Use Programs: Motivations and Change Processes Several meta-analyses (e.g., Arce et al, 2020;Arias et al, 2013;Babcock et al, 2004;Cheng et al, 2019) have indicated mixed results on the efficacy of perpetrator programs, partially attributable to methodological issues, such as effectiveness being measured in a range of ways. Given this, there have been calls to improve the way that perpetrator programs are evaluated (Akoensi et al, 2013;Hester et al, 2014) as well as calls to better understand how perpetrators change (McGinn et al, 2020) and their motivations to enact change (Forsdike et al, 2018). Qualitative research can add nuance to evaluations by illuminating motivations and change processes.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding processes of change, a range of qualitative studies has found that men who perpetrate violence have cognitive distortions (e.g., about relationships, responsibility, and blame), which are the products of deeply embedded core beliefs. It is argued that men who have perpetrated IPA use these cognitive distortions to minimize and justify violence (Forsdike et al, 2018;Parra-Cardona et al, 2013). Men report that perpetrator programs have led to them becoming more aware of their own cognitive distortion and core beliefs (McGinn et al, 2020;Parra-Cardona et al, 2013), although it is unclear how far being made aware of these beliefs and distortions led to change.…”
Section: Introductionmentioning
confidence: 99%